Sophie Kuijken - Donnadieu, Marc 1960-; Crenn, Julie 1982- (Éditions Racine, 2018)
I like to paint people. I like reading them simply by watching them"--Sophie Kuijken. At first glance, Sophie Kuijken paints portraits. But these representations are anything but innocuous. The artist constructs her works by collecting images gleaned from the internet. She uses photographs of people who inspire her and by multiplying identities, creates singular personalities. The ambiguity of these images is accompanied by a great concern for precision, revealed by the fold of a garment, the choice of a colour, and Kujiken's mastery of the play of shadows and lights. Exhibition: Galerie Nathalie Obadia, Paris, France (07.01. - 11.03.2017) / Art Brussels 2017, Belgium (21.-23.04.2017)
Keywords: Kuijken, Sophie -- 1965-